Evaluación de la actividad antioxidante y antimicótica del extracto hidroalcohólico de las hojas de Bunchosia armeniaca (ciruelo cansa boca) - Poma Avila, Oliver Pierre (2018)
In the present work, the evaluation of the antioxidant and antifungal activity of the hydroalcoholic extract of the Bunchosia armeniaca leaf "plum de cansa boca" was determined. The leaves were collected from the Botanical Garden of Medicinal Plants "Rosa Elena de los Rios Martinez" of the Faculty of Pharmacy and Biochemistry of the National University of Trujillo, Department of La Libertad. The hydroalcoholic extracts were prepared by reflux. Antioxidant capacity was determined by the method developed by Brand-Williams, whose spectrophotometric readings were performed at 520 nm. The results were expressed in percentage of capture of the radical 2,2-Diphenyl-1- Picrilhidrazilo (DPPHº) at the concentrations of 0.02 mm, 0.04 mm, 0.06 mm, 0.08 mm and 0, 1 Mm. finding an IC50 of 0.4810 mg / mL having an improved antioxidant capacity with the articles found. The antifungal effect was performed on strains of Cándida albicans ATCC 10231 using the Kirby-Bauer method (agar diffusion). For the antifungal effect, experimental group I (25% hydroalcoholic extract) showed an average of 7.176 mm in diameter, for experimental group II (hydroalcoholic extract at 50%) it showed an average of 7.836 mm in diameter and for experimental group III (hydroalcoholic extract at 75%) of higher concentration with an average of 8.236 mm in diameter